VALUE UNITY AS THE BASIS FOR THE FORMATION OF CIVIC IDENTITY IN STUDENT YOUTH - Okushko, Tetiana (Theoretical and Methodical Problems of Children and Youth Education, 2024)
This article addresses the relevant issue of value unity as the foundation for forming the civic identity of student youth. The research was conducted within the scientific framework of the Laboratory of Moral, Civic and Intercultural Education of the National Academy of Educational Sciences of Ukraine. The purpose of this article is to reveal the essence of value unity in the formation of civic identity among student youth and to present the results of the national survey, “Civic Identity at the Crossroads of Change” conducted by the Laboratory of Moral, Civic and Intercultural Education of the Institute of Problems on Education o the National Academy of Educational Sciences of Ukraine in 2024. To achieve the goals and objectives of the study, theoretical methods (analysis, synthesis, comparison, generalization, systematization), empirical methods (survey, ranking), and methods of mathematical statistics were used for data processing and generalization. The article highlights key aspects of value unity in forming civic identity in student youth. This will require a qualitative update in content and the introduction of innovative forms, methods, and tools for civic and patriotic education in the conditions of existential challenges and fundamental social changes. It will also contribute to forming civic identity in children and youth within and outside the educational system. A range of issues that will require further resolution to improve civic and patriotic education for children and student youth is outlined. The practical significance of the research is that the materials can be used in general secondary, extracurricular, and higher education institutions, as well as in the work of youth departments within state administrations and united territorial communities, public organizations, and social services working with children and youth.